Avaliação da toxicidade reprodutiva do extrato seco obtido das folhas de pimenta pseudocaryophyllus (Gomes) Landrum (Myrtaceae), quimiotipo (E)-metilisoeugenol, em ratas Wistar - (:unkn) unknown (Universidade Estadual de Goiás, 2016)
Leaves of Pimenta pseudocaryophyllus (Gomes) Landrum (Pp), a Myrtaceae specie, has been traditionally used in Brazilian folk medicine to prepare calming, digestive and emmenagogue teas. In the last decades studies have established the botanical caracterization, the phytochemistry profile and the pharmacological potential of Pp, that includes antibiotic, anxiolytic, antidepressant, antioxidant, antinociceptive and anti-inflammatory properties. Therefore, there was no scientific information about Pp toxicity, especially during pregnancy. Therefore, this study aimed at investigating the reproductive toxicity of the dry leaf extract of Pp, (E)-methyl isoeugenol chemotype (EPpm), during the organogenesis period of Wistar female rats. In addition, the (E)-methyl isoeugenol chemotype identification was verified by the presence of its chemical markers in high performance liquid chromatography (HPLC) and the EPpm production by spray drying had its yield calculated. For these purposes, leaves of Pp were collected, dryed and powdered. The powder obtained was percolated in ethanol 95%. The ethanolic extract was vaccum concentrated and spray drying. At this point, forty-two dams were divided in four groups which received EPpm by gavage at the doses of 2000, 2500 or 3000 mg/kg from gestational day (GD) 6 through 15 (organogenesis period). The control group only received the vehicle. Maternal clinical signs of toxicity, body weight gain, food and water consumption were recorded from GD 0 to 21. On GD 21, the dams were submitted to cesarean section, euthanized and examined for the reproductive parameters. Furthermore, blood samples were collected through cardiac puncture for analysis of biochemistry parameters related to hepatic and renal markers. The fetuses, in turn, were removed from the uterus, macroscopically examined, and submitted to diaphanization processes and alizarin red staining. Then, the offsprings were evaluated for skeletal variations and malformations. The results confirm the (E)-methyl isoeugenol chemotype identification by the presence of chemical markers gallic acid, catechin, quercitrin and (E)-methyl isoeugenol in the EPpm chromatography profile. The spray drying technique preserved the phytocomplex components and showed a satisfactory yield of 12,49%. Concerning the toxicological evaluation, the results showed that, in the organogenesis period, there were a marked reduction in the mean maternal body weight gain in all treatment groups when compared with control (p ≤ 0,01). The dams treated with 2000 mg/kg increased the water consumption when compared to the dams treated with 3000 mg/kg and the control group (p ≤ 0,05). There were no significant differences in the food consumption, neither n biochemical and reproductive parameters of the dams treated with EPpm. Moreover, no changes were found in the external evaluation of the offsprings. In regard of the skeletal analysis, it was observed in the offsprings the presence of significant and no treatment-related variations as rudimentary ribs, bipartite sternebra, incomplete ossification of sternebra, metacarpals, metatarsals and anterior phalanges (p ≤ 0,0084). In conclusion, the EPpm treatment, in the doses of 2000, 2500 or 3000 mg/kg, showed low maternal toxicity (decrease of the maternal body weight gains during the organogenesis) and no interference in the external or skeletal development of Wistar rats.
Keywords: Toxicidade materna; Toxicidade do desenvolvimento; Desempenho reprodutivo; Parâmetros bioquímicos; Variações esqueléticas; Maternal toxicity; Developmental toxicology; Reproductive outcome; Biochemistry parameters; Skeletal variations; CIENCIAS DA SAUDE; CIENCIAS DA SAUDE::FARMACIA